Community Transformation: Asian American Community Leaders - Brian Ahn (Adult Education Research Conference, 2023)
Utilizing in-depth interviews, theories, and concepts in analysis, this study examines how a group of Asian American leaders transformed their community politically, socially, and economically.
Keywords: learning-from-experience; community; leadership; mentorship; collaboration